2021
DOI: 10.1038/s41598-021-87831-6
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the impact of induced magnetic flux and Fourier’s and Fick’s theories on the Carreau-Yasuda nanofluid flow

Abstract: The current study analyzes the effects of modified Fourier and Fick's theories on the Carreau-Yasuda nanofluid flow over a stretched surface accompanying activation energy with binary chemical reaction. Mechanism of heat transfer is observed in the occurrence of heat source/sink and Newtonian heating. The induced magnetic field is incorporated to boost the electric conductivity of nanofluid. The formulation of the model consists of nonlinear coupled partial differential equations that are transmuted into coupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 44 publications
(44 reference statements)
2
9
0
Order By: Relevance
“…Therefore, rising in 𝑊 𝑒 𝑐 deemed as reason for decaying in the viscosity of the fluid, which enlarges the axial velocity 𝑞 𝜁 correspondingly. This demeanor is totally consistent to the behavior that reported in [15], [32], and [35]. Figure 3 portrays the impact of the velocity slip parameter𝛽 1 𝑠 on the axial velocity 𝑞 𝜁 .…”
Section: Numerical Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Therefore, rising in 𝑊 𝑒 𝑐 deemed as reason for decaying in the viscosity of the fluid, which enlarges the axial velocity 𝑞 𝜁 correspondingly. This demeanor is totally consistent to the behavior that reported in [15], [32], and [35]. Figure 3 portrays the impact of the velocity slip parameter𝛽 1 𝑠 on the axial velocity 𝑞 𝜁 .…”
Section: Numerical Discussionsupporting
confidence: 85%
“…one found that an enhancement in 𝑁 𝑏𝑟 enlarges 𝜃 𝐸 . This resultant outcome is compatible with that illustrated by [9], [15] and [33]. Finally, 𝜃 𝐸 has a progressive reduction for diverse values of both 𝐷 𝑓 as well as 𝑆 𝑜𝑟 .…”
Section: Numerical Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Samrat et al 12 investigated the heat transfer (HT) in hybrid NF and gave the simultaneous solutions. Some application of NF applied for different physical problems were studied in 13 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Hayat et al [17] considered this phenomenon for the peristaltic flow of fourth-grade fluid. Bashir et al [18] considered magnetic flux and Fourier/Ficks theories on effects in the peristaltic motion of Carreau-Yasuda nanofluid. Zahid et al [19] showed informative results by taking hybrid nanofluid with entropy effect.…”
Section: Introductionmentioning
confidence: 99%